Patrones de prescripción de hormonas tiroideas en una población colombiana - Valencia Marulanda, Jhon Edward; Jiménez-Canizales, Carlos Eduardo; Salazar, Victoria; Romero, Diego; Machado-Alba, Jorge Enrique (Revista Médica de Risaralda, 2015)
Patrones